The Effect of Self-Efficacy and Sense of Community towards Students’ Higher Order Thinking Skills - Windy Antika Aryani; Wayan Suana (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
This study aims to find out the effect of students' self-efficacy and students’ sense of community on higher order thinking skills in physics learning. The research is correlational research with two variables, those are independent and dependent variables. The independent variables is self-efficacy and sense of community, while the dependent variable is the higher order thinking skills. The research is carried out in a month by using blended learning method towards the students of X IPA SMA Bandarlampung. The data obtained were tested using single linear regression and multiple linear regression. A single linear regression test of self-efficacy towards higher order thinking skills obtained R value that is .142. The correlation coefficient is positive. R value of .142 is in the very low range. This shows that self-efficacy is positive but its effect is very low, so it has no influences on the population. The single linear regression test of sense of community towards the higher order thinking skills obtained an R value of .242. The correlation is positive. R of .242 is in the very low range of influence, so it has no influences on the population. The multiple linear regression test of self-efficacy and sense of community towards higher order thinking skills obtained the coefficient of determination (R) of .270. R of 0.270 is in the very low range that means its no influence on the population. The calculated F value is 2.405. This value is smaller than the value of F table at a 5% significance level that is 3.15. This shows that there is a positive but no influences between self-efficacy and sense of community on students' higher order thinking skills. From those three relationships, no one has an influence on students' higher order thinking skills, but beyond the focus of the researchers.